The pedagogical approaches to shift ethnic boundaries: exploring pedagogical experiences of Malaysian youths in school and university / Fatimah Mohd Tajuddin, Kartini Aboo Talib @Khalid and Shazlin Amir Hamzah - Mohd Tajuddin, Fatimah; Aboo Talib @Khalid, Kartini; Amir Hamzah, Shazlin (Universiti Teknologi MARA, 2024)
This research paper investigates the pedagogical experiences of Malaysian youths in school and university that were perceived to shift their ethnic boundaries and facilitate interethnic engagement. Although the education system is perceived to be an important social integration platform, studies indicate a concerning trend of ethnic polarization among Malaysian youths in school and university. Therefore, this study investigates the pedagogical approaches that were experienced by selected Malaysian youths that were able to shift their ethnic boundaries and pave the way for interethnic engagement. There are three research objectives for this study which are (i) to identify the pedagogical approaches that thickens ethnic boundaries (ii) to identify the pedagogical approaches that thins ethnic boundaries and (iii) to identify the pedagogical approaches that dissolves ethnic boundaries. This study utilizes the Ethnic Boundaries concept by Mansor (2021) as an analytical tool to evaluate the pedagogical approaches experienced by the youths in shifting their ethnic boundaries. A qualitative methodology employed key informant interviews with eight selected Malaysian youths and two focus group interviews from the eight selected Malaysian youths consisting of five youth informants for each group. The study’s results found three categories of pedagogical experiences shared by the informants, which are segregative, interactive, and critical pedagogical approaches. The findings also highlight the role of the performing arts as a potential pedagogical tool to facilitate interethnic engagement and develop crucial consciousness on interethnic relations among Malaysian youths.